Solving Method of H-infinity Model Matching Based on the Theory of the Model Reduction - Li Linzhi; Cao Xinjun (Institute of Advanced Engineering and Science, 2014)
People used to solve high-order model matching based on control theory, it is too difficult. In this paper, we use model reduction theory to solve high-order model matching problem, A new method to solve model matching problem based on the theory of the model reduction is proposed． The simulation results show that the method has better applicability and can get the expected performance．